Peran Baznas Kabupaten Lingga dalam Meningkatkan Perekonomian Masyarakat Kabupaten Lingga - Saputra, Agus (Jurnal Indragiri Penelitian Multidisiplin, 2026)
Overcoming poverty is something that every country must pay attention to through policies regulated by the government, but it cannot yet be utilized by all people. With the BAZNAS institution in Lingga Regency, poverty can be minimized by strengthening the community's economy through cooperation, social care and empowerment. In Islamic teachings, people are encouraged to share and help each other in order to create mutual prosperity. Values ​​such as alms, zakat and mutual assistance are an important basis for building a more just and prosperous life for the entire community. Paying zakat, infaq and alms is a form of Muslim obedience to religious teachings. The implementation of this worship aims to create social awareness, help people in need, and create equal distribution of welfare in accordance with the principles of justice in Islam and one of the missions of Lingga Regent Regulation Number 21 of 2011, with the aim of the Lingga district government in alleviating poverty in the district. This research uses a qualitative descriptive approach based on literature review and discussion results. Research findings show that BAZNAS' role is quite significant in the management and distribution of zakat funds to support community welfare. This research method uses descriptive qualitative based on literature and discussion. The results of this research are that the role of BAZNAS Lingga Regency has been carried out optimally by looking at the results of reports from the past few years, but it has not been fully effective and efficient in achieving optimal goals.